2015
DOI: 10.1016/j.mehy.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxic resistance training: Is metabolic stress the key moderator?

Abstract: Traditionally, researchers and practitioners have manipulated acute resistance exercise variables to elicit the desired responses to training. However, recent research indicates that altering the muscular environment during resistance training, namely by implementing a hypoxic stimulus, can augment muscle hypertrophy and strength.Intermittent hypoxic resistance training (IHRT), whereby participants inspire hypoxic air during resistance training, has been previously demonstrated to increase muscle cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 41 publications
(57 reference statements)
1
45
0
Order By: Relevance
“…Since blood flow restriction is usually matched with low intensity resistance training, the changes in cross sectional area and strength may not be accompanied by a concomitant increase in connective tissue strength. This is due to decreased mechanical loading through low intensity resistance training used with blood flow restriction (Scott et al, 2015a), therefore the strength of muscles and connective tissue will adapt disproportionately. Increased tensile strength of the tendon might be expected to maintain the safety of the tendon under increasing loads (Buchanan and Marsh, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since blood flow restriction is usually matched with low intensity resistance training, the changes in cross sectional area and strength may not be accompanied by a concomitant increase in connective tissue strength. This is due to decreased mechanical loading through low intensity resistance training used with blood flow restriction (Scott et al, 2015a), therefore the strength of muscles and connective tissue will adapt disproportionately. Increased tensile strength of the tendon might be expected to maintain the safety of the tendon under increasing loads (Buchanan and Marsh, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In IHRT research, these contrasting findings may result from differences in the structure of exercise. If sufficient repetition volume during sets is not performed, the contraction time during which metabolites accumulate is decreased, and if inter-set rest periods are too long there is a greater chance for intramuscular metabolites to be removed into circulation and PCr resynthesis to occur (Scott et al, 2014, 2015a). Likewise, if adequate recovery is given between efforts during RSH training protocols, the replenishment of PCr stores may occur despite the hypoxic conditions (Girard et al, 2011).…”
Section: Impacts Of Hypoxia On Metabolic Processesmentioning
confidence: 99%
“…This is supported by recent research that has demonstrated heightened integrated electromyography response during moderate-load IHRT compared to the same exercise in normoxia (Scott et al, 2016). If more motor units are recruited during training, a larger portion of the muscle will be stimulated to adapt (Scott et al, 2015a). Cell swelling is another potential mediator for muscle hypertrophy, resulting from metabolite accumulation within the cells and a resultant inflow of water to equilibrate the osmotic gradient (Loenneke et al, 2012).…”
Section: Roles Of Metabolic Stress In Adaptations To Exercisementioning
confidence: 99%
See 2 more Smart Citations